Approaches to the Medieval Self : Representations and Conceptualizations of the Self in the Textual and Material Culture of Western Scandinavia, c. 800-1500 - Bandlien, Bjørn; Eriksen, Stefka Georgieva; Langsholt Holmqvist, Karen (2020)
The main aim of this book is to discuss various modes of studying and defining the medieval self, based on a wide span of sources from medieval Western Scandinavia, c. 800-1500, such as archeological evidence, architecture and art, documents, literature, and runic inscriptions. The book engages with major theoretical discussions within the humanities and social sciences, such as cultural theory, practice theory, and cognitive theory. The authors investigate how the various approaches to the self influence our own scholarly mindsets and horizons, and how they condition what aspects of the medieval self are 'visible' to us. Utilizing this insight, we aim to propose a more syncretic approach towards the medieval self, not in order to substitute excellent models already in existence, but in order to foreground the flexibility and the complementarity of the current theories, when these are seen in relationship to each other. The self and how it relates to its surrounding world and history is a main concern of humanities and social sciences. Focusing on the theoretical and methodological flexibility when approaching the medieval self has the potential to raise our awareness of our own position and agency in various social spaces today.